Strategic Planning and its Importance in Building Institutional Work in the National Insurance (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The aim of the research is to identify the reality of strategic planning in the National Insurance Company and its importance in building institutional work and to identify the requirements that enable this company to successfully implement strategic planning and the obstacles that limit its application and then achieve the marketing objectives of this company. This study started from the fact that there is a problem represented by the main question that was stated.                                                          Is the company interested in planning its insurance activities in the long term in order to achieve a balance between the cash benefits collected from the installments with the cash compensation that the company spends to compensate for the insured losses?                                                                                                                              The summary of the research is that the National   Insurance Company does not have sufficient flexibility to expand its insurance activities represented in issuing new insurance documents and new types and marketing these documents. The reason for this is due to its ownership of the state and it is subject to the laws and regulations it sets in this field, in addition to the fact that the National Insurance Company does not rely on planning its activities. Insurance for long-term periods, and the company's lack of experience and competence in its field of work, which leads to difficulties in applying modern scientific methods.                                                                              The research reached many recommendations, the most important of which are;   The need to use modern technology in order to develop local   production methods, in addition to the company's reliance on planning its insurance activity, not only in the short term, but rather it must develop long-term plans in order to ensure the success of its work in this field. As well as the need for the company to adopt the proper scientific approach and develop its marketing methods in a competitive environment with other companies and the comparison between alternatives.